Stress, Coping, and Well-being in Teachers and School Administrators - Woloshyn, Vera; Savage, Michael; Maich, Kimberly; Penney, Sharon (Alberta Journal of Educational Research, 2023)
This study explored educators’ self-reported state of well-being, perceived stressors, and use of coping strategies. Data collection consisted of an online survey and semi-structured focus groups. In total, 115 educators completed the online survey and 18 educators participated in the focus groups. Educators reported overall experiences of poor well-being, low resilience, high levels of compassion fatigue, and high levels of emotional exhaustion. Participants identified ongoing stressors related to supporting student learning and well-being, overseeing classroom environments, navigating limited community-based resources and supports, and managing increasing administrative demands and functions. Implications of the findings for practice are discussed. Keywords: Stress; Coping; Well-being; Educators; Mental Health Cette étude a exploré l'état de bienêtre déclaré par les éducateurs, les facteurs de stress perçus et l'utilisation de stratégies d'adaptation. La collecte des données a consisté en une enquête en ligne et des groupes de discussion semi-structurés. Au total, 115 éducateurs ont répondu à l'enquête en ligne et 18 éducateurs ont participé aux groupes de discussion. Les éducateurs ont fait état d'expériences globales de malêtre, de faible résilience, de niveaux élevés d'usure de la compassion et de niveaux élevés d'épuisement émotionnel. Les participants ont identifié des facteurs de stress permanents liés au soutien de l'apprentissage et du bienêtre des élèves, à la supervision des environnements de classe, à la navigation dans les ressources et soutiens communautaires limités, et à la gestion des demandes et fonctions administratives croissantes. On discute des implications des résultats pour la pratique. Mots clés : stress ; adaptation ; bienêtre ; éducateurs ; santé mentale